Croatian wine market, support policy and specific obstacles to wine exports - Lucijano, Jakšić L; Njavro, Mario; Hrvoje, August (Applied Studies in Agribusiness and Commerce, 2016)
In this paper, analysis of Croatian wine sector in period 2006-2013 is conducted through the record of wine production, exports and imports together with Government support measures. In the light of Croatian EU membership together with opening of EU wine market and global wine market, recommendations for further discussion of support measures for small and medium winemakers are given.